The Correlation between Students’ Reading Habits and Their Ability in Writing Analytical Exposition Text - Ana Rohmah; Riya Risqi Setyaningrum; Riryn Fatmawaty (Universitas Islam Negeri Palopo, 2025)
Reading is essential for students’ academic development, particularly in enhancing their writing ability. Nevertheless, many students are reluctant to read and encounter difficulties in writing analytical exposition texts, which require critical thinking and clear organization. This research investigates the correlation between students’ reading habits and their ability to write analytical exposition texts in the Indonesian EFL context, specifically at MAN 1 Lamongan during the academic year 2023/2024. The research employed a quantitative method with a correlational design. Participants were 34 eleventh-grade students from the Ilmu Bahasa dan Budaya (IBB) class, selected purposively. Data were obtained through a reading habits questionnaire and a writing test of analytical exposition texts, and then analyzed using SPSS 23. The findings reveal that students’ reading habits were generally categorized as “good,” while their writing ability fell into the “excellent” category. A strong and significant positive correlation was identified between reading habits and writing ability. These results highlight the importance of cultivating students’ reading habits as a foundation for developing stronger writing skills. This research contributes to English language education in Indonesia by emphasizing the role of reading in enhancing writing proficiency. Teachers are encouraged to implement effective and engaging strategies that foster reading motivation, thereby improving students’ ability to produce well-structured analytical writing. The findings may also serve as a valuable reference for future research with a broader scope.